Re/assembling the pregnant and parenting teenager : narratives from the field(s) - Kamp, Annelies; McSharry, Majella (Peter Lang AG, 2018)
This book offers a re/assemblage of what is, can be and should be known about teenage pregnancy and parenting in the twenty-first century. It examines the narratives of young men and women in the USA, the UK, Aotearoa New Zealand and Ireland, all sites of elevated concern around what is often articulated as the 'problem' of teenage parenting.